Developing youth football players : Tap the full potential of your young footballers - Wein, Horst (United States : Human Kinetics, 2007)
Coach your young players to their maximum potential! Developing Youth Football Players combines proven coaching methods with engaging games that allow young athletes to develop their skills, understand team play and appreciate the sport
Includes bibliographical references.
Keywords: Soccer for children--Coaching; Soccer for children--Training